(untitled) (Педагогіка вищої та середньої школи, 2007)
The article demonstrates the real situation with pedagogical testing in Ukrainian higher educational establishment. In author’s opinion, testing can be the most effective method of scientifically grounded control over specialist’s training process if it will be found appropriate conditions to its investigation into practical use.